Breaking barriers: the role of technological education in advancing arab women in Israel - Nassar, Mozin; Hidalgo-Ariza, Mª Dolores (EDMETIC, 2024)
This study investigates the role of technology integration in educational frameworks on empowering Arab women in Israeli society, focusing on their participation in the high-tech sector. It tests two hypotheses: that technology integration boosts Arab Israeli women's interest in STEM and high-tech careers, and that it enhances their societal and economic empowerment. Despite the success of Israel's high-tech industry and advancements in education, Arab women remain underrepresented in this sector. The research utilizes a structured questionnaire to assess digital literacy's impact on Arab Israeli women's career aspirations in high-tech. The findings suggest that integrating technology into education can significantly increase Arab women's interest in STEM fields, supporting their greater involvement in the high-tech industry. The study underscores the importance of continued technological integration in education to promote diversity and inclusion in the high-tech sector. However, limitations include a regional focus and a quantitative approach, indicating the need for further research to fully understand the empowerment of Arab women in the Israeli high-tech industry.